Comparing the fundamental movement skill proficiency of children with intellectual disabilities and typically developing children: a systematic review and meta‐analysis. - Kavanagh, H.; Manninen, M.; Issartel, J. (Journal of Intellectual Disability Research, 2023)
Background: Children around the world, particularly those with intellectual disabilities (ID), are exhibiting poor motor skill proficiency. Compared with typically developing children (TDC), children with intellectual disabilities (CwID) are 65% more likely to exhibit low levels of motor competence. The purpose of this meta‐analysis was to compare the motor skill proficiency levels, in terms of fundamental movement skills (FMS) of CwID to TDC. FMS are the building blocks required for lifelong participation in sport and physical activity. Method: The meta‐analysis was conducted according to PRISMA statement guidelines. 6 electronic databases were searched and 16, 679 studies were found. A total of 26 studies (total participants n = 3,525) met the inclusion criteria. A multivariate maximum likelihood multivariate random effects model was fitted to the data using the metafor package in R. Results: The study showed that the standardised mean difference (Hedges' g) in FMS between TDC and CwID is large (g = 1.24; CI 95% [.87, 1.62]). Specifically, significant differences between the two groups emerged in all five outcomes: (1) total locomotor score, (2) total object manipulation score, (3) balance, (4) run skill and (5) throw skill. Conclusions: Further investigation into effective intervention strategies is required in order to reduce the magnitude of difference in motor skill proficiency between the two groups. In addition to developing, implementing and evaluating these interventions, researchers need to work hand in hand with national governing bodies (NGB) of sport and policy makers to ensure that teachers and coaches are being provided with opportunities to upskill in the area of FMS.